Coexistence of chronic cutaneous lupus erythematosus and frontal fibrosing alopecia - Luciana Lima do Nascimento; Milvia Maria Simões e Silva Enokihara; Mônica Ribeiro de Azevedo Vasconcellos (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Lupus erythemathosus is a chronic, relapsing disease with acute, subacute, and chronic lesions. Effluvium telogen occurs in the setting of systemic activity of the disease, and cicatricial alopecia results from discoid lesionsin on the scalp. Other types of alopecia, like alopecia areata, may rarely be found in lupus. Frontal fibrosing alopecia is characterized by frontotemporal hairline recession and eybrow loss. Histophatologically, it cannot be differentiated from lichen planopilaris.It is controversial whether frontal fibrosing alopecia is a subtype of lichen planopilaris.. A pacient with chronic lichenoid lupus erythematosus is described with clinical, histophatological and dermoscopic features of frontal fibrosing alopecia.We have not been able to find in the literature cases of frontal fibrosing alopecia as a clinical manifestation of lupus.